The democratic virtues of the Christian right - Shields, Jon A. (Princeton University Press, 2009)
The Christian Right is frequently accused of threatening democratic values. But in The Democratic Virtues of the Christian Right, Jon Shields argues that religious conservatives have in fact dramatically increased and improved democratic participation and that they are far more civil and reasonable than is commonly believed. Shields interviewed leaders of more than thirty Christian Right organizations, observed movement activists in six American cities, and analyzed a wide variety of survey data and movement media. His conclusions are surprising: the Christian Right has reinvigorated American.